2022
DOI: 10.1002/pul2.12174
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioral processes predict anxiety and depression in patients with pulmonary hypertension

Abstract: Emotional and psychological difficulties cannot fully be explained by disease‐related factors in people with pulmonary hypertension (PH). This study examined the relationship between anxiety, depression, demographic, objective and subjective PH factors, and self‐reported cognitive and behavioral processes, which have been associated with mood in clinical and nonclinical samples. This is a secondary analysis of baseline data from 77 adults with PH who took part in a randomized controlled trial of a self‐help in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…11 Participants' cognitions and behaviors from the CBP-Q also predicted anxiety and depression, even after controlling for PH-specific factors such as functional class or self-reported dyspnea. 12 Taken together, the results suggest that individual difference variables in people with PH can help to identify those at risk of developing mood disturbance, as well as serve as a target for intervention.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…11 Participants' cognitions and behaviors from the CBP-Q also predicted anxiety and depression, even after controlling for PH-specific factors such as functional class or self-reported dyspnea. 12 Taken together, the results suggest that individual difference variables in people with PH can help to identify those at risk of developing mood disturbance, as well as serve as a target for intervention.…”
Section: Introductionmentioning
confidence: 79%
“…Indeed, in a recent study, prospective and retrospective analyses of data collected as part of a self‐help intervention using cognitive‐behavioral therapy (CBT) for anxiety in PH, found that changes in unhelpful cognitions and behaviors (as measured by the cognitive behavioral processes questionnaire: CBP‐Q) mediated the relationship between intervention group (CBT vs. waitlist) and a reduction in anxiety and depression 11 . Participants' cognitions and behaviors from the CBP‐Q also predicted anxiety and depression, even after controlling for PH‐specific factors such as functional class or self‐reported dyspnea 12 . Taken together, the results suggest that individual difference variables in people with PH can help to identify those at risk of developing mood disturbance, as well as serve as a target for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Treadmill training was continued on the regular floor until the patient could ambulate with minimum support (FAC-score 2). In an intention to treat analysis (ITT), the median time to independent ambulation was 6 (3-9) days in the intervention group and 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days in the UC group (P 5 .063). The authors noted that although not significant in the ITT analysis, the difference in time to independent ambulation was considerable between the intervention and UC group, because of the large hazard ratio (1.97) and Kaplan-Meier curve.…”
Section: Critical Carementioning
confidence: 99%
“…Promising results of cognitive therapies on dyspnea have also been reported in other cardiovascular and pulmonary diagnoses such as asthma, interstitial lung disease, pulmonary hypertension, and HF. [20][21][22][23]…”
Section: Clinical Relevancementioning
confidence: 99%
“…In other words, PH patients will constantly experience a life of sudden exacerbation of symptoms, complex and repeated treatments, and serious complications (Aguirre‐Camacho & Moreno‐Jiménez, 2018). These will undoubtedly place patients in a perpetual state of chronic psychological stress, especially fear/panic (Rawlings et al, 2022a), which is completely different from the traditional psychological disorders of anxiety and depression that can occur in people without the disease (Liu et al, 2021). Olsson et al (2021) reported a 15.2% prevalence of panic disorder in patients with PAH, approximately eight times that of the general population.…”
Section: Introductionmentioning
confidence: 99%